Small head size and delayed body weight growth in wild Japanese monkey fetuses after the Fukushima Daiichi nuclear disaster - Shin-ichi Hayama (Nature Portfolio, 2017)
Abstract To evaluate the biological effect of the Fukushima Daiichi nuclear disaster, relative differences in the growth of wild Japanese monkeys (Macaca fuscata) were measured before and after the disaster of 2011 in Fukushima City, which is approximately 70 km from the nuclear power plant, by performing external measurements on fetuses collected from 2008 to 2016. Comparing the relative growth of 31 fetuses conceived prior to the disaster and 31 fetuses conceived after the disaster in terms of body weight and head size (product of the occipital frontal diameter and biparietal diameter) to crown-rump length ratio revealed that body weight growth rate and proportional head size were significantly lower in fetuses conceived after the disaster. No significant difference was observed in nutritional indicators for the fetuses’ mothers. Accordingly, radiation exposure could be one factor contributed to the observed growth delay in this study.